2023
DOI: 10.1111/sipr.12099
|View full text |Cite
|
Sign up to set email alerts
|

Gender essentialism and benevolent sexism in anti‐trans rhetoric

S. Atwood,
Thekla Morgenroth,
Kristina R. Olson

Abstract: The past half‐decade has seen an exponential rise in proposed and debated anti‐trans legislation in the United States. These bills are often positioned at the center of divisive political debates between Republicans (who typically support these laws) and Democrats (who typically do not). In the process of discussing these debates, there has been widespread dissemination of anti‐trans rhetoric that has the potential to impact public opinion. In this review, we approach this rhetoric through the lens of social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 199 publications
0
2
0
Order By: Relevance
“…Effective advocacy against these laws necessitates a unified effort among TGE people, allies, and health care professionals, emphasizing intersectionality to understand the varied experiences within TGE communities and advocate for their rights. It’s crucial to confront damaging beliefs and laws, promoting an approach that respects and includes TGE individuals by uniting efforts and adopting advocacy informed by an understanding of intersectionality (Atwood et al, 2024; Brightman et al, 2023; Mowat et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Effective advocacy against these laws necessitates a unified effort among TGE people, allies, and health care professionals, emphasizing intersectionality to understand the varied experiences within TGE communities and advocate for their rights. It’s crucial to confront damaging beliefs and laws, promoting an approach that respects and includes TGE individuals by uniting efforts and adopting advocacy informed by an understanding of intersectionality (Atwood et al, 2024; Brightman et al, 2023; Mowat et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that the influx of antitrans legislation attempting to prohibit trans women in predominantly cisgender women spaces (ex. women's sports and bathrooms) is motivated by gender essentialist and benevolent sexist views (Atwood et al, 2024). These very belief systems are antithetical to feminist goals and serve to maintain the current gender hierarchy.…”
Section: Further Considerationsmentioning
confidence: 99%